2005
DOI: 10.1042/bj20041241
|View full text |Cite
|
Sign up to set email alerts
|

TEB4 is a C4HC3 RING finger-containing ubiquitin ligase of the endoplasmic reticulum

Abstract: In the present study, the human TEB4 is identified as a novel ER (endoplasmic reticulum)-resident ubiquitin ligase. TEB4 has homologues in many species and has a number of remarkable properties. TEB4 contains a conserved RING (really interesting new gene) finger and 13 predicted transmembrane domains. The RING finger of TEB4 and its homologues is situated at the N-terminus and has the unconventional C4HC3 configuration. The N-terminus of TEB4 is located in the cytosol. We show that the isolated TEB4 RING domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
141
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(149 citation statements)
references
References 60 publications
7
141
1
Order By: Relevance
“…1B and 7A). As reported previously (42), WT and C9A co-localized with calnexin, and overexpression resulted in localization throughout the ER network. The G885L and N890A mutants both co-localized with calnexin and had patterns indistinguishable from WT MARCH6 -3xFLAG.…”
Section: The Doa10 Cte Promotes Efficient Deg1supporting
confidence: 85%
See 2 more Smart Citations
“…1B and 7A). As reported previously (42), WT and C9A co-localized with calnexin, and overexpression resulted in localization throughout the ER network. The G885L and N890A mutants both co-localized with calnexin and had patterns indistinguishable from WT MARCH6 -3xFLAG.…”
Section: The Doa10 Cte Promotes Efficient Deg1supporting
confidence: 85%
“…Endogenous MARCH6 and Exogenous MARCH6 CTE Mutants Localize to the ER-The human ortholog of Doa10, MARCH6 (TEB4), is also believed to be an ERAD ubiquitin ligase, although localization of the endogenously expressed protein to the ER has not been directly demonstrated (42). Like Doa10, MARCH6 appears to have 14 transmembrane domains with the N-terminal RING domain and C-terminal tail protruding into the cytoplasm (11).…”
Section: The Doa10 Cte Promotes Efficient Deg1mentioning
confidence: 99%
See 1 more Smart Citation
“…Analogies to yeast Hrd1p͞Der3p further break down, because there is no identifiable human Cue1p ortholog. More recently, a mammalian Doa10p ortholog, TEB4, has been identified that may play a role in MHC regulation (19,20).…”
mentioning
confidence: 99%
“…In yeast, the Hrd1 and Doa10 E3 ubiquitin ligases are central components of the membrane-associated ERAD machinery [67,68]. In mammals, no less than 16 E3 ligases have been implicated in the ERAD pathway, including HRD1 [69], gp78 [70], and TEB4 [71,72]. Constituents of the HRD1 complex are similar to those in yeast and include the adaptor protein SEL1L (similar to Hrd3) [73], the rhomboid pseudoprotease Derlin-1 (a homolog of Der1) [74,75], the scaffold protein Herp (Usa1) [76,77] and other lumenal and cytosolic factors.…”
Section: Eradmentioning
confidence: 99%